Efektivitas Metode LOK-R untuk Meningkatkan Kemaanpuan Berliterasi Siswa MTsN 2 Aceh Utara Kelas VII - Mahyuni, Mahyuni; Astuti, Nia; Yuhafliza, Yuhafliza (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
The purpose of this research is to find out whether the iLOK-R learning model has an effect on the learning outcomes of students in the text of ifantasy stories. This type of research uses a qualitative approach with an experimental research method, that is, it only uses an experimental group without a control group and a comparison group. iThe research design used was a one-group pretest-posttest design. iWhile the data collection techniques used were tests, observations, and documentation. The data analysis technique used descriptive statistical data analysis, normality test, it-test, and hypothesis test. The results of this research show that there is a significant effect on the learning outcomes before and after the test. iThe percentage of students who passed in the pretest is 10%, and the percentage of students who passed in the posttest is 100%. iIt can be concluded that iH0 is rejected and iH1 is accepted. iThat means there is a significant influence between the iLOK-R learning model on the learning outcomes of students in the text of ifantasy stories.